2007
DOI: 10.2139/ssrn.982109
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health and Behavior, HIV/AIDS, and Poverty in Africa

Abstract: This paper examines the complex linkages of poverty, reproductive/sexual health and behavior, and HIV/AIDS in Africa. It addresses the following questions:(1) what have we learned to date about these links and what are the gaps in knowledge to be addressed by further research; (2) what is known about the effectiveness for HIV prevention of reproductive health and HIV/AIDS interventions and policies in Africa; and (3) what are the appropriate methodological approaches to research on these questions. With regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 146 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…The HIV/AIDS literature identifies other predisposing and enabling factors that may fuel the spread of the disease. These are: the poor state of general reproductive health services that leads to a large burden of sexually transmitted infections (STIs); poorly developed health services—to the extent that a large proportion of the population do not know their HIV status; and biological factors (Anyanwu et al ., ; Oster, , ; Glick, ; Ferry et al , ). One of the most highlighted reproductive health characteristics of SSA is the large number of untreated non‐HIV STIs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIV/AIDS literature identifies other predisposing and enabling factors that may fuel the spread of the disease. These are: the poor state of general reproductive health services that leads to a large burden of sexually transmitted infections (STIs); poorly developed health services—to the extent that a large proportion of the population do not know their HIV status; and biological factors (Anyanwu et al ., ; Oster, , ; Glick, ; Ferry et al , ). One of the most highlighted reproductive health characteristics of SSA is the large number of untreated non‐HIV STIs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other pathways to HIV infection relate to the state of overall health services. Glick () notes that the majority of the adult population in SSA has never been tested for HIV/AIDS despite the outbreak of the disease more than 30 years ago. Thus, there is limited knowledge about HIV/AIDS status, which exacerbates the spread of the disease, as mentioned earlier.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Certain individuals (and families) may be more likely to suffer an AIDS death. For example, poverty is often cited as a key driver of transmission of HIV/AIDS (Fenton 2004), although the evidence of this link tends to show the opposite association (as noted by Shelton, Cassell, and Adetunji 2005; Wojcicki 2005; Gillespie, Kadiyala, and Greener 2007; and Glick (2007). In their study of eight sub-Saharan African countries, Mishra et al (2007) find that wealthier adults are more likely to be infected with HIV, although this association is very weak after controlling for urban/rural residence and education.…”
Section: Empirical Strategymentioning
confidence: 99%
“…A general finding of this literature is that widows in Western societies are often vulnerable to poverty (Hurd & Wise, 1989McDonald et al, 2000;Weir & Willis, 2000). Another analysis of widows explores household dissolution and the role of widows in conjunction with the HIV/AIDS pandemic (Glick, 2007). HIV widows in five East and Southern African countries were found to be more vulnerable to poverty and land shortage than other households (Mather et al, 2004a), while widows have not been found to be worse-off in Mozambique (Mather et al, 2004b).…”
Section: War Widowsmentioning
confidence: 99%